Penyelesaian Keterlambatan Pembayaran Kredit Di Bank Rakyat Indonesia Kantor Cabang Pembantu (KCP) Borong Kabupaten Manggarai Timur - Kade, Angelina Febriani; Jacob, Yossie M Y; Dju Bire, Chatryen M (Law Faculty, Nusa Cendana University, 2025)
This study analyzes the obstacles and efforts to overcome late credit payments at BRI KCP Borong, East Manggarai Regency, using empirical legal research methods and a descriptive qualitative approach. The results of the study identified two groups of factors causing delays: (1) internal factors, including an ineffective monitoring system, complicated restructuring procedures, lack of customer education, and technical disruptions; (2) external factors in the form of business competition, emergencies, economic fluctuations, customer characteristics, and inappropriate use of credit. BRI KCP Borong implements a comprehensive strategy through preventive efforts (strict feasibility analysis, education, and digital services) and repressive efforts (gradual collection, restructuring, mediation, and litigation). The research findings indicate that a gradual approach in accordance with the Banking Law and the Civil Code can balance the protection of the rights of both parties, although the recording of OJK's SLIK remains a serious consequence for customers. This study recommends strengthening the synergy between improving the bank's internal system, increasing customer capacity, and improving regulations in order to create a more responsive and fair banking system.